Functionalization of Tile‐based DNA Nanocages with Gold Nanoparticles (AuNPs) to Form AuNP Cluster‐DNA Cage Hybrids. Issue 8 (8th June 2020) - Yu, Yang; Lei, Yunxiang; Dong, Qiang; Li, Yulin
Abstract: Attaching functional nanomaterials onto tile‐based DNA nanocages to form hybrids consisting of DNA nanocages and nanomaterial clusters with well‐defined compositions might not only integrate the functions of each component, but also potentially lead to new emergent properties and applications. Herein, we report a general and facile hybridization‐driven approach for functionalizing tile‐based nanocages with gold nanoparticles (AuNPs) to form AuNP cluster‐DNA cage hybrids. AuNP tetramer‐DNA tetrahedron hybrids and AuNP octamer‐DNA octahedron complexes have been successfully fabricated. Our hybridization‐based strategy could in principle be extended to fabricate various hybrids with designable compositions and structures due to the diversity of tile‐based nanocages and the great variety of functional nanomaterials that could be modified with DNA, which should hold the promise of greatly promoting the research of bio/nanoassembly. Abstract : A general and facile hybridization‐based approach for functionalizing tile‐based nanocages with gold nanoparticles (AuNPs) is reported. AuNP tetramer‐DNA tetrahedron hybrids and AuNP octamer‐DNA octahedron complexes have been successfully fabricated.